Kenali, Pahami dan Terapkan Edukasi Keluarga Berencana dalam SAFARI KB serta Pemeriksaan Kesehatan Dasar di Puskemas Lembang - Gusnawati, Yesi; Raehan, Raehan (Yayasan Inspirasi El Burhani, 2025)
Introduction: One of the important problems faced by developing countries, such as Indonesia, is population explosion. The population explosion resulted in a rapid population growth rate.. The National Family Planning Movement aims to control the rate of population growth and also to improve the quality of human resources Objective: Raising public awareness on family planning and early detection of non-communicable diseases through education, contraceptive services, free basic health checks, and promotion of healthy lifestyles. Method: The counseling activity was conducted using an interactive lecture method, accompanied by a Q&A session, leaflet distribution, and The outreach activity Recognize, Understand and Apply Family Planning Education in family planning safaris and basic health checks at Pkm Lembang was carried out on August 22 2025 for 25 PUS people who were given an explanation about family planning and basic health checks. The activity took place over one day at the lembang health center Hall and targeted couples of reproductive age (CRA). Family planning services such as contraceptive injections and pill distribution were also provided. Result: Based on observations during the activity, this community service activity resulted in increased knowledge and understanding of PUS regarding the importance of family planning for reproductive health and PUS understands that using family planning has many benefits such as being able to regulate pregnancy spacing, maintain maternal reproductive health, and reduce maternal and infant mortality rates. Conclusion: It is necessary to carry out regular evaluation and monitoring to determine the level of public understanding of the importance of family planning and early detection of non-communicable diseases. It is necessary to utilize social media to disseminate information about family planning and early detection of non-communicable diseases and reach the wider community.